Arbiters of Truth: Government Fact-checking in the South Asia - Alam, Ahmed Shatil; Bilal, Umer; Hossain, Mohammad Zahid (Department of Communications, Universitas Islam Indonesia, 2025)
This study documents fact-checker prioritization of political agendas in government-run fact-checking in India and Pakistan. Government fact-checkers in both countries debunked the content critical of the government but failed to mention specific methods and sources of verification. The research also discussed the implications of government-run fact-checking in overall fact-checking practices andnorms. This research also shows that Indian and Pakistani fact-checkers, both government-run and independent, interest areas are confined to issues related to politics, entertainment, sports, health, religion, economics, and international affairs.